The Nurse's Role in Prognosis-Related Communication in Pediatric Oncology Nursing Practice. (September 2020) - Newman, Amy R.; Linder, Lauri; Haglund, Kristin
The experiences of pediatric oncology nurses with prognosis-related communication (PRC) remain largely unknown. The purpose of this article is to report results of focus groups wherein 15 pediatric oncology nurses from three Midwestern pediatric cancer programs provided descriptions of PRC and how they experience PRC within their daily practice. Data from focus groups were analyzed via an interpretive descriptive approach, which resulted in three themes: (1) nurses' operational definition of PRC, (2) nurses' roles in PRC, and (3) nurses' preparation for engagement in PRC. From discussions within the focus groups, nurses recognized that PRC occurs across a continuum. Nurses distinguished that the definition of PRC expands beyond simply reporting life expectancy to describing the consequences of cancer- and treatment-related toxicities and effects. When nurses are not actively invited by their physician partners to participate in PRC, nurses will often develop workarounds to ensure that they understand what was said to patients and families. This allows them to function more effectively as supporters, advocates, and informants. Nurses described little preparation to participate in such challenging conversations. Pediatric oncology nurses need to acknowledge and embrace that they are an integral part of PRC. Interprofessional communication training is necessary to enhance the comfort and confidence of nurses engaging in PRC.